Chlorine-functionalized keto-enamine-based covalent organic frameworks for CO2 separation and capture. Issue 47 (5th October 2018) - Shinde, Digambar B.; Ostwal, Mayur; Wang, Xinbo; Hengne, Amol M.; Liu, Yang; Sheng, Guan; Huang, Kuo-Wei; Lai, Zhiping
Abstract : Enhancing the CO2 uptake and selectivity of the keto-enamine-based COFs by chlorination. Abstract : We report highly chemically and thermally stable chlorine-functionalizedCAA-COF-1 andCAA-COF-2 . The chlorine-functionalized COFs exhibited enhanced CO2 uptake (by ∼28–44%) in comparison with their pristine COF analogues (TpPa-1 andTpBd ). Column breakthrough experiments reveal thatCAA-COF-1 andCAA-COF-2 display a high CO2 /N2 (10/90) gas mixture selectivity of 95 and 54, respectively. Additionally, CAA-COF-1 exhibits a CO2 /CH4 (10/90) column breakthrough selectivity of 29.